New approach for the measurement of long-term alcohol consumption trends: Application of wastewater-based epidemiology in an Australian regional city. (1st February 2020) - Zheng, Qiuda; Tscharke, Benjamin J.; Krapp, Catharina; O'Brien, Jake W.; Mackie, Rachel S.; Connor, Jason; Mueller, Jochen F.; Thomas, Kevin V.; Thai, Phong K.
Highlights: Alcohol consumption monitored over 6 years using 42 daily wastewater samples/year. WBE showed higher alcohol consumption during weekends and holidays vs weekdays. Declining trend in alcohol consumption observed by WBE is consistent with other data sources. Alcohol consumption estimated by WBE is better once correction for sewer degradation is included. Abstract: Background: Wastewater-based epidemiology (WBE) provides complementary information to traditional self-report methods for estimating substance use within a population. WBE was applied to estimate the consumption of alcohol in an Australian rural city (population estimated 100, 000) over 6 years. Methods: A total of 352 wastewater samples were analysed from a wastewater treatment plant located in South-East Queensland, Australia, from 2012 to 2017. The concentration of an alcohol biomarker, ethyl sulphate, was quantified by liquid chromatography tandem mass spectrometry and used to estimate per-capita consumption. The WBE results were compared with alcohol consumption estimates based on national taxation data and self-reported national survey data in Australia. Results: Average daily alcohol consumption estimated by WBE was between 19 and 30 mL/person/day for the population aged 15 years and older during the six-year period. Alcohol consumption decreased 4 % per annum on average over the study period. Our data showed higher rates of consumption on weekends and public holidays when compared to consumption between Monday and Thursday. The comparative trend of WBE data was consistent with the national alcohol survey and taxation statistics on alcoholic beverages over the same period. Conclusions: A clear decline in alcohol consumption in the catchment was observed during the sampling period, which reflected similar changes in consumption from taxation statistics and self-report survey data. Expected variations in weekly consumption and public holidays were also identified. This study demonstrates the potential of WBE for long-term monitoring of alcohol consumption in evaluating the effectiveness of local and national alcohol policies and prevention programs.